PLASMA FIBRONECTIN AND URINE GLYCOSAMINOGLYCANE LEVELS IN PATIENTS WITH OSTEOARTHRITIS - Ali Gür,; Kemal Nas,; Remzi Çevik,; Ferda Erdoğan,; Ayşegül Jale Saraç, (Archives of Rheumatology, 2001)
Osteoarthritis is characterized by the progressive destruction of articular cartilage. There is a loss of cartilage proteoglycan content and disorganization of the collagen network, as well as an increase in non-collagenous protein such as fibronectin. In this study we investigate whether these connective tissue inter-components would help the diagnosis in determining degenerative changes, and to reveal their importance in distinguishing osteoarthritis and their follow up as well as the correlation between plasma fibronectin level and urinary glycosaminoglycan excretion. In this study, plasma fibronectin and urine glycosaminoglycane levels were determined spectrophotometrically in 65 osteoarthritis patients (mean age: 52,13±7,20 years), and 41 healthy (mean age: 46,21±9,85 years) control subjects. The mean levels of fibronectin (mg/ml) were 436,49± 115,51 in patients with osteoarthritis, 302,3 ± 61,1 in the control group. The ratio of urine glycosaminoglycan excretion to creatinine (g/mol) was 2,76±1,15 in patients with osteoarthritis, 1,96±0,8 in the control group. Plasma fibronectin levels were significantly higher in osteoarthritis when compared to the control group (p<0,001). The ratio of urinary glycosaminoglycans excretion to creatinine levels in patients with osteoarthritis were significantly greater when compared with control group (p<0,001). There were significant correlation between the age and plasma fibronectin levels (r=0,41, p<0,01), urinary glycosaminoglcans excretion (r=-0,42, p<0,01) of patients with osteoarthritis . Our findings suggest that determination of urinary glycosaminoglycans excretion and plasma fibronectin might be an important parameter in degenerative diseases, especially in the diagnosis and followup of osteoarthritis.